MUSYAWARAH PERENCANAAN PEMBANGUNAN DI DESA TELAGA ARUM KECAMATAN SEPONTI KABUPATEN KAYONG UTARA - Mukhid Ansori E.42008066 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
AbstractThe title of the research is " Development Planning Meeting in Desa Telaga Arum Kecamatan SepontiKabupaten Kayong Utara ". The purposes of this research is to know and analiyze how the implementation ofDevelopment Planning Meeting in Desa Telaga Arum Kecamatan Seponti Kabupaten Kayong Utara, starting from thepre Development Planning Meeting , implementation Development Planning Meeting to after Development PlanningMeeting. Method that used to conduct this research a qualitative approach to describe the overall implementation ofrural development planning meetings. The data was collected using observation, interviews, and documentation. Theresearch location in Desa Telaga Arum Kecamatan Seponti Kabupaten Kayong Utara. Subjects were parties to knowand be involved in rural development planning meetings, both at the village and higher levels of government such as thedistrict governments and local governments. The results of the field study showed that the implementation ofDevelopment Planning Meeting Desa in Telaga Arum has not optimally, it can be identified by the lack of communityinvolvement in determining priorities for actions to be filed in the district Development Planning Meeting. Telaga ArumVillage Community participation in Development Planning Meeting still low because only community representativeswho participated in Development Planning Meeting. realization of development priorities have not been up it a lessconstrained budget, and did not get a response at the higher levels of government.Keywords: Development Planning Meeting , community participation, and development priorities.